Analyzing Research Trends in Smart Construction Safety: A Topic Modeling Approach - Hyun Jeong Seo; Young-Geun Yoon (Buildings)
The construction industry is increasingly embracing smart technologies to enhance safety, efficiency, and sustainability. Despite their potential, the practical integration of technologies such as digital twins, the Internet of Things (IoT), and big data into construction safety management systems remains insufficiently explored. This study investigates how these technologies can be effectively implemented to improve safety outcomes. A systematic review of the literature is conducted, culminating in the development of a conceptual framework for integrating smart technologies into safety systems. The study highlights the application of digital twins, the IoT, and big data for real-time monitoring, predictive risk management, and resource optimization. The findings reveal that these technologies significantly enhance construction site safety by proactively identifying hazards, reducing accidents, and improving resource allocation. Moreover, smart technologies contribute to environmental sustainability by optimizing energy use and lowering carbon emissions. This research underscores the dual benefits of technological integration, advancing both safety and sustainability objectives. While the study provides theoretical insights and practical implications, further empirical research across diverse construction environments is necessary to validate and refine the proposed framework.